Securing Maritime Autonomous Surface Ships: Cyber Threat Scenarios and Testbed Validation - Seongmin Lee; Yonghun No; Juwon Cho; Guckhyeon Jin; Jeongho Kim; Jeongmin Lee; Sanghyun Jeon; Faisal Abdulaziz Alfouzan; Kyounggon Kim (IEEE Access)
The maritime industry is undergoing rapid digital transformation, with Maritime Autonomous Surface Ships (MASS) at the forefront, introducing unprecedented cybersecurity challenges. This study investigates the unique characteristics and cybersecurity requirements of MASS, presenting a tailored approach to address these vulnerabilities effectively. To validate the proposed solution, a testbed environment replicating real-world shipboard networks was developed, incorporating eight attack scenarios designed using the MITRE ATT&CK ICS framework. Among these, the most critical scenario was systematically evaluated, demonstrating the solution’s robustness and practical applicability. By bridging the gap between theoretical models and real-world implementations, this research provides a replicable methodology and foundational tools to enhance the cybersecurity of autonomous maritime systems, supporting the safe and reliable adoption of MASS in the global maritime industry.